2018
DOI: 10.1016/j.bpsc.2018.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Orbital and Medial Prefrontal Cortex Functional Connectivity of Major Depression Vulnerability and Disease

Abstract: Background Pathophysiology models of major depression (MD) center on the dysfunction of various cortical areas within the orbital and medial prefrontal cortex (OMPFC). While independent structural and functional abnormalities in these areas are consistent findings in MD, the complex interactions among them and the rest of the cortex remain largely unexplored. Methods We used resting state functional magnetic resonance imaging (fMRI) connectivity to systematically map alterations in the communication between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 88 publications
3
16
0
Order By: Relevance
“…SMN connectivity with the DAN and VIS connectivity with the CON were especially indicative of emotional abuse/neglect and physical abuse/neglect, respectively. These systems have been related to treatment outcomes in affective disorders, risk, and family history of depression (34), and to functional domains, including error monitoring and top-down attentional control (35). We speculate that physical abuse/neglect and emotional abuse/neglect may have induced abnormal activation of sensory systems, such as the sensorimotor and visual cortex, and to have dysregulated connectivity with ventral and dorsal attention systems.…”
Section: Discussionmentioning
confidence: 99%
“…SMN connectivity with the DAN and VIS connectivity with the CON were especially indicative of emotional abuse/neglect and physical abuse/neglect, respectively. These systems have been related to treatment outcomes in affective disorders, risk, and family history of depression (34), and to functional domains, including error monitoring and top-down attentional control (35). We speculate that physical abuse/neglect and emotional abuse/neglect may have induced abnormal activation of sensory systems, such as the sensorimotor and visual cortex, and to have dysregulated connectivity with ventral and dorsal attention systems.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the result of decreased ReHo within motor cortex in the present study may be a neuroimaging reflection of anxiety. Although several studies have demonstrated abnormal cerebral connectivity involving the visual cortex and midbrain in depression [ 49 , 50 ], rare clinical studies reported altered ReHo in the two regions. Since the pathological alterations of the visual cortex and midbrain exist in depression [ 51 53 ], there may be also differences between the rat model and patients with depression in the visual cortex and midbrain Reho signal.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, distinct sub-regions of the cerebellum are selectively involved in different primary emotions, including positive and negative emotions ( Adamaszek et al, 2017 ). In addition, as a cortical hub, the insula carries the information of dyspnea and emotions ( Borsook et al, 2016 ), and FC between the cerebellum and insula could play an important role in depression in asthmatic patients ( Zhong et al, 2017 ; Samara et al, 2018 ). Specifically, in our study, this FC pattern was reversed by GCBT and positively correlated with depressive severity in patients who received treatment.…”
Section: Discussionmentioning
confidence: 99%